The Altars Are Holding the Nation in Captivity': Zambian Pentecostalism, Nationality, and African Religio-Political Heritage - Kaunda, Chammah J. (Religions, 2018)
The study draws on ontocracy political theory to investigate Zambian Pentecostal interpretations of politics as a sacred realm of contestations between forces of good and evil. It argues that Zambian Pentecostal theology of nationality is a continuation of traditional African religio-cultural ethnonational heritage. It demonstrates how Zambian Pentecostal theology of nationality is based on socio-historically constructed conceptions that drew their foundation from traditional myths, symbols and cultures. It concludes that Zambian Pentecostalism has failed to make distinctions among various types of human authorities, thereby promoting a theology of nationality that mystifies the source of the political authority of the presidents of the nation, who are perceived as absorbing both secular and spiritual responsibilities.